Environmental arts therapy the wild frontiers of the heart - Heginworth, Ian Siddons; Nash, Gary (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2020)
"Environmental Arts Therapy: The Wild Frontiers of the Heart describes what happens when we take the creative arts therapies and the people whom we work with out of doors in order to provide safe, structured and accompanied creative therapeutic healing experiences. The theoretical themes are developed along with illustrated examples of clinical practice across a variety of settings and locations. The work is introduced and co-edited by a pioneer in the field, Ian Siddons Heginworth, who describes the emergence of environmental arts therapy and its growth across the British Isles supported through the training course based in London. The following 12 chapters are written by contributing authors and creative arts therapy practitioners working with children, adults and elders in schools, adult mental health and private practice in Britain and Europe. A central focus of the book is the clinical populations and settings in which clinicians work, and it also describes the health benefits as well as the challenges faced when working out of doors. This is a book about the emergence of a new creative therapy modality in the British Isles. It shows the value of working with the natural cycles and seasons, using an integrative arts approach including dramatic enactment, role-play, poetry, art-making with natural materials, storytelling, and the use of bodywork through movement, sound, rhythm and the voice, all held and reflected by our encounters with and in nature. It is about our relationship with nature, creativity and therapeutic healing and is written for trainers, trainees and practitioners in the creative arts, psychotherapy and ecotherapy"--Page 4 of cover.
Foreword / Mary-Jayne Rust -- Acknowledgements -- Introduction by the editors / Ian Siddons Heginworth and Gary Nash -- Part I. Environmental arts therapy in context : Turning: the emergence and growth of environmental arts therapy in the British Isles / Ian Siddons Heginsworth -- Weaving the threads of theory and experience: a review of the literature / Gary Nash -- Part II. Childhood, love and attachment: the heart of the matter : The wild inside: offering children natural materials and an ecopsychological understanding of self within art therapy / Lydia Boon -- EarthWays: environmental arts therapy for repairing insecure attachment and developing creative response-ability in an insecure world / Lia Ponton -- Bringing the outside in: reflecting upon Mother within a pilot group in environmental arts therapy / Michelle Edinburgh -- Part III. Feminine and masculine : putting feeling first : Meeting the wounded feminine: trauma-informed environmental arts therapy as an approach to working with physical illness / Susie Thompson -- The wood between the worlds: encountering the wounded healer in environmental arts therapy / William Secretan -- The tapping on the window: environmental arts therapy and the integrated self / Auriel Eagleton -- Part IV. The cycle of the year: working with the seasons : Taking art therapy outdoors: a Circle of Trees / Gary Nash -- Creating connections: introducing environmental arts therapy into London's green spaces / Simon Woodward -- Space to move, explore and create: taking art therapy into the outdoor environment in adult mental health services / Pamela Stanley -- Part V. Elders and endings: the wild road on : Trees of life and death: a journey into the heart of Transylvania to use environmental arts therapy with groups of adults and staff in palliative care / Hammah Monteiro -- Growing elders: the cultivation and collaboration of an elder women's group in the woods / Deborah Kelly and Vanessa Jones -- Epilogue / Ian Siddons Heginworth.
Includes bibliographical references and index.
Keywords: Art therapy; Art therapy -- Europe -- Methods; Art therapy -- Great Britain -- Methods; Recreational therapy; Nature -- Therapeutic use; Outdoor life -- Therapeutic use